Effectiveness of Self Compassion-Based Interventions on Elderly People: A Literature Review - Bahadır Yılmaz, Emel (Magyar Gerontológia, 2025)
This review article is designed to evaluate the impact of self-compassion-based interventions on the physical, psychological, and social health of older adults. Recent studies support that high self-compassion enhances life satisfaction in older adults, strengthens resilience against physical and emotional challenges, and fosters a more positive adaptation to age-related changes. The evidence the impact of self-compassion-based interventions on the health of older adults shows that these approaches help elderly individuals better manage stress, control negative emotions, and reduce symptoms of depression, ultimately fostering greater resilience and life satisfaction. Integrating self-compassion with cognitive-behavioral or motor-based activities amplifies these effects, contributing to improved forgiveness, acceptance, and emotional adjustment. Furthermore, such interventions address important dimensions of mental health, including feelings of loneliness and the ability to form positive relationships, which are especially relevant for older individuals facing health challenges or living in residential care. Collectively, these findings underscore the value of self-compassion-focused programs in supporting successful aging and holistic mental health in later life. Given these findings, integrating self-compassion and mindfulness-based approaches into mental health programs for the elderly can offer valuable benefits.